(untitled) (Research, Society and Development, 2020)
During its historical trajectory, Brazilian indigenous school education has earned its official recognition as a specific, differentiated, intercultural and bilingual education. It has sought in the curriculum in action, the valorization of its traditional ethnoconceptions. Ethnomathematics in indigenous school education in the early years of elementary school I is configured as the central objective of this study, aiming to present socio-cultural artifacts as a strategy to expand the process of teaching and learning the contents of teaching in a Pataxó indigenous school in Bahia. The theoretical and methodological framework fits within a qualitative approach. Regarding the objectives, it is aligned with exploratory research and within the procedures of ethnographic research associated with action research. The results revealed a significant 87% improvement in procedural evaluations. The discourses of 100% of the researched students revealed greater interest in learning the mathematical contents through the use of socio-cultural artifacts of the Pataxó ethnicity. It was found that the use of artifacts as concrete material established a positive approach between the cultural mathematics of indigenous education and school mathematics; it was found in the voices of the community that the use of socio-cultural artifacts made it possible to value, recognize and disseminate their traditional mathematical knowledge in class. It was concluded that specific socio-cultural artifacts promoted significant learning in the educational processes of teaching and learning the mathematical contents prescribed by the current National Common Curriculum Base for the initial years. This has brought greater motivation for students to learn, as well as the adaptation of mathematics to the culture and socio-cultural identity of this ethnic group.